Artificial Intelligence in Writing: Students' Writing Competencies and Voices - Saiful Marhaban; Teguh Sulistyo; Oktavia Widiastuti (JEELS (Journal of English Education and Linguistics Studies), 2025)
Integrating artificial intelligence (AI) in writing instructions may lead to an ongoing debate among scholars. However, the rapid development of technologies of AI technologies cannot be avoided in daily lives, including written language productions. This paper, then, tries to highlight two cases: the impacts of AI and process-based approach on students’ writing competencies and what students perceive about the intervention. The study, which involved 27 Indonesian English language majors, used a mixed-methods approach that included both qualitative and quantitative data. The results showed that the integration of AI and a process-based approach significantly improved global, local, and overall issues. Surprisingly, local issues, which include grammar, vocabulary, and mechanics, had the greatest effect of all. In addition, students have a positive perception of AI in writing instruction. For them, AI promotes their autonomy and creativity through the use of ChatGPT and AI-generated feedback such as Deepl and Grammarly. The implications are also presented and discussed.